UX/UI Development of the website design of the faculty of arts of the H.S. Skovoroda Kharkiv national pedagogical university - Zhytienova, Natalia (Professional Art Education, 2021)
The main aim of the article is the improvement of the existing design of the Faculty of Arts of H.S. Skovoroda Kharkiv National Pedagogical University website. Methods & methodology. Such research methods as subject-analytical for studying structural and illustrative sources; a terminological technique for a clear understanding of the essential features of design; a psychological method of verbal determination the nature of the visual sensation from the final stage of site design development were used. The scientific novelty consists in the comprehensive analysis of educational sites of higher education institutions of Ukraine in the direction of art education. Identification of modern trends in UX/UI design in the development of artistic sites. Highlighting the necessary structural elements of the development of the Faculty of H.S. Skovoroda Kharkiv National Pedagogical University website. The results of the study proved that for the development of the UX/UI design of the website of the Faculty of Arts of the H.S. Skovoroda Kharkiv National Pedagogical University it is necessary to use various structural elements, such as: emotional design (use of visually "live" elements to induce feelings and reactions from users); geometric structure (use of classic geometric elements for accentuation); split-screen design (using a conditionally split-screen design (using a conditionally split screen into two panels of content that collapses into a vertical block in responsive design); increasing the content of the text (returning multi-level headings, etc.); new fonts (avoiding the classics and using serifs, changing the size from word to word, using a semi-transparent font overlapping an opaque one, adding bold and italic writing); adaptation to new gadgets (providing high-quality enlarged images for adaptive design); unique micro-interaction (the presence of tactile reviews in adaptive design, i.e. the ability to change the shade for different states of the program, visualization of loading the desired page, adding animation during the transition, the presence of an original reaction to pressing certain buttons on the site).